Pricing carbon in a multi-sector economy with social discounting - Kalsbach, Oliver; Rausch, Sebastian (Discussion paper, 2021)
Economists tend to view a uniform emissions price as the most cost-effective approach to reducing greenhouse gas emissions. This paper offers a different view, focusing on economies where society values the well-being of future generations more than private actors. Employing analytical and numerical general equilibrium models, we show that a uniform carbon price is efficient only under restrictive assumptions about technology homogeneity and intertemporal decision-making. Non-uniform pricing spurs capital accumulation and benefits future generations. Depending on sectoral heterogeneity in the substitutability between capital and energy inputs, we find that optimal carbon prices differ widely across sectors and yield substantial welfare gains relative to uniform pricing.
Keywords: Graue Literatur